Dealing with Complexity – Knowledge, design, and management of the built environment - Cesare Sposito; Francesca Scalisi (Agathón, 2024)
AGATHÓN issue number 16 is a collection of essays, studies, research and projects on ‘Dealing with Complexity | Knowledge, design, and management of the built environment’. Complexity (from the Latin verb ‘plectere’ = to weave, ‘cum’ = together) is a condition in which many elements intertwine together to form a unit. The ‘complexity’ of the Planet’s condition is evident: climate change, according to Amitav Ghosh (2017), is not a danger in itself but rather represents a ‘threat multiplier’ that stresses and amplifies the instability and insecurity already present in some areas of the world, even more so because many industrialised countries have already greatly exceeded their relative ‘biocapacity’, effectively becoming ‘ecological debtors’.